Effects of Brachiaria decumbens leaf meal supplementation on the health, blood biomarkers, and relative telomere length of broiler chickens raised in tropical environments - Eric, Lim Teik Chung; Ong, Yee Ling; Mohamed M., Alghirani; Abu Kassim, Nafeesa; Loh, Teck Chwen; Abdullah, Faez Firdaus Jesse; Kamalludin, Mamat Hamidi (South African Society for Animal Science, 2023)
The main goal of this investigation was to determine the effects of Brachiaria decumbens leaf meal on the health performance, blood biomarkers, and relative telomere length of broiler chickens raised in tropical conditions. A total of 300, day-old, male, Ross 308 broilers were divided into six groups and given various feeding regimens based on a completely randomized design model. T1 commercial feed was devoid of antibiotics (negative control) whereas T2 commercial feed was supplemented with 100 mg/kg oxytetracycline (positive control). Commercial diets supplemented with 25, 50, 75, and 100 mg/kg of powdered B. decumbens leaf meal was given to the birds in treatments T3, T4, T5, and T6, respectively. Throughout the 42-day study, there were a few occurrences of leg problems, diarrhoea, and fatalities, but no statistical association was detected. The growth performance, leucocyte profile, immunoglobulin and cytokine concentrations, and relative telomere length, however, differed substantially among treatments.T3 broilers fed with diets supplemented with 25 mg/kg of B. decumbens leaf meal exhibited the best growth performance (highest final body weight and body weight gain; lowest cumulative feed conversion ratio), leucocyte profiling (increased total white blood cell count, monocytes, and basophil count; decreased heterophil to lymphocyte ratio), immunoglobulins (up-regulated IgG, IgA, and IgM), cytokines (increased IL4 and IL7), and telomere length. In conclusion, B. decumbens leaf meal can be used instead of antibiotics to enhance the growth and health of broilers raised in hot, humid conditions.